(untitled) (Materiali di Estetica. Terza serie, 2024)
The article reflects on Fulvio Papi’s philosophical approach, highlighting his dedication to simplifying complex ideas to reveal underlying truths. The author recounts personal interactions that demonstrate Papi’s ability to engage deeply yet succinctly with philosophical concepts, enhancing understanding and discussion. The article underscores Papi’s impact through his commitment to clarity and ethical simplicity, leaving a lasting legacy in philosophical discourse.